Growing inclusive businesses in the Philippines: The role of government policies and programs - Roehlano M. Briones (Philippine Institute for Development Studies (PIDS), 2016)
Inclusive business (IB) is a private sector approach to providing goods, services, and livelihoods on a commercially viable basis, either at scale or scalable, to people at the base of the pyramid by making them part of the value chain of companies' core business as suppliers, distributors, retailers, or customers. There is keen interest in IBs, both in the public and private spheres, as a strategy for inclusive growth. The Department of Trade and Industry is setting up an accreditation system to certify business models as IB, based on an evaluation tool, initially for three priority sectors: agribusiness, housing, and tourism. This paper analyzes the economic and development potential of IBs, and describes existing programs and policies of the government in terms of openness to IB. It then makes several recommendations for short-term IB promotion, as well as long-term measures to support IB in the Philippines.
Keywords: 330; Inclusive growth; inclusive business; micro; small; and medium enterprises; small farmers and fishers; base of the pyramid; industry promotion